Leveraging Jasper Reports for Dynamic Financial Reporting in Modern Tolling Systems: A Technical Implementation Guide - Umesh Waghmode (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive technical implementation guide for leveraging Jasper Reports in modern tolling systems to enhance dynamic financial reporting capabilities. The article explores the evolution of electronic toll collection infrastructures and their integration with advanced reporting systems. It examines the core components of dynamic reporting architecture, including data flow pipelines, real-time parameter handling, and system integration points. The article delves into report customization and format optimization techniques, highlighting the importance of stakeholder-specific templates and dynamic parameter implementation. The article also investigates financial analysis capabilities through AI-driven smart information systems and big data technologies, focusing on daily ledger management and revenue tracking mechanisms. Advanced analytics features, including ranking functions and hierarchical data visualization, are analyzed for their impact on operational efficiency. The implementation of automated report scheduling and distribution frameworks is discussed, along with their security features and reliability metrics. The article concludes by examining the operational benefits achieved through these implementations, including improved decision support, stakeholder communication, and cost reduction through automation.